LEXICOGRAMMAR AND TEXT STRUCTURE IN DESCRIPTIVE TEXT WRITTEN BY JUNIOR HIGH SCHOOL STUDENTS - Gewinn Tiroma Mahdalena Sigalingging; Berlin Sibarani; Siti Aisah Ginting (Universitas Negeri Medan, 2020)
ABSTRACTThe objectives of this study were the descriptive lexicogrammar and text structure written by Junior High School students. This study was conducted by descriptive qualitative method. The source of the data was the descriptive text written by the students where they describe the pictures of cats and sunflower. The technique of data collection was observation. The technique of data analysis was Interactive Model by Miles and Huberman (2014).The findings show that the students used all the descriptive lexicogrammar, they are Tense, Verbs, Adjectives, Adverbs and Reference. The finding also show that all the students written descriptive text by applying all descriptive text structure components, they are Classification, Appearance, Behaviour, Attribute, and Location. The students of grade 7, 8, and 9 of Junior High School used five components of lexicogrammar on descriptive text, namely, Tense, Verb, Adjectives, Adverbs, and Reference, but, the use of tense has not been used properly up to grade 9 because there is found that there are incorrect subject verb-agreement and incorrect choosing and using lexicogrammar. In term of text sructure, the students used five components of text structure, they are, Classification, Appearance, Behaviour, Attribute, and Location, but, the use of Classification have not yet been used correctly since there is still mistake related to place the classification on the text.Keywords: Lexicogrammar, Text Structure, Descriptive Text